Development and Validation of a Stability Indicating RP-HPLC Method for the Determination of Two Sun Protection Factors (Koptrizon and Tinosorb S) in Topical Pharmaceutical Formulations Using Experimental Designs. (25th May 2013) - Roy, Chinmoy; Chakrabarty, Jitamanyu
Abstract : A novel, simple, validated stability indicating HPLC method was developed for determination of Koptrizon and Tinosorb S. Stability indicating power of the method was established by forced degradation study. The chromatographic separation was achieved with Waters X Bridge C 18 column, by using mobile phase consisting of a mixture of acetonitrile : tetrahydrofuran : water (38 : 38 : 24, v/v/v). The method fulfilled validation criteria and was shown to be sensitive, with limits of detection (LOD) and quantitation (LOQ) of 0.024 and 0.08  μ g mL − 1 for Koptrizon and 0.048 and 0.16  μ g mL − 1 for Tinosorb S, respectively. The developed method is validated for parameters like precision, accuracy, linearity, solution stability, specificity, and ruggedness as per ICH norms. Design expert with ANOVA software with linear model was applied and a 2 3 full factorial design was employed to estimate the model coefficients and also to check the robustness of the method. Results of the two-level full factorial design, 2 3 with 10 runs including two-centre-point analysis based on the variance analysis (ANOVA), demonstrated that all three factors, as well as the interactions between retention time of Koptrizon, Tinosorb S, and USP plate count for Koptrizon, are statistically significant.